Functional Characterization of the Gustatory Sensilla of Tarsi of the Female Polyphagous Moth Spodoptera littoralis - Seada, Mervat A.; Ignell, Rickard; Al Assiuty, Abdel Naieem; Anderson, Peter (Frontiers in Physiology, 2018)
Contact chemoreception is crucial for host choice selection in insects and is guided by input from gustatory receptor neurons, GRNs, housed in gustatory sensilla. In this study, the morphology and response spectra of individual tarsal sensilla on the fifth tarsomere of females of the moth Spodoptera littoralis were investigated. Two distinct morphological types of gustatory sensilla, TI and TII, were identified. Extracellular electrophysiological recordings were performed on each sensillum type using three sugars, two bitter substances and salt. Three distinct functional classes (TIα, TIβ, TII) were characterised, using cluster analysis based on the response spectra of three of the four responding GRNs. While each functional type of sensillum housed GRNs responding to salt, sugars and bitter compounds, the identity of these cells differed among the functional classes. Interestingly, an interaction between the GRNs responding to sugar and caffeine was found in both TIβ and TII sensilla, when binary mixtures were tested. This study provides a functional screening of the tarsal gustatory sensilla, showing a differentiation between sensilla on the tarsi of S. littoralis, providing the female moth with information that can facilitate host plant choice decisions.